The Financial Consequences of Online Review Aggregators: Evidence from Yelp Ratings and SBA Loans - Huang, Ruidi (Management Science, 2024)
This paper demonstrates the financial and real consequences of online review aggregators. Exploiting a regression discontinuity design that overcomes the endogenous relationship between Yelp reviews and Small Business Administration loan outcomes, I show that higher coarse Yelp ratings lead to improved loan terms and performance. Specifically, a one-half-star increase in Yelp ratings corresponds to a 25-basis-point decrease in loan spread and 6% lower collateral requirements. The effects are more pronounced when banks have less borrower information. Higher Yelp ratings also contribute to increased consumer demand and the likelihood of future business openings. These findings indicate that online review aggregators influence both consumer choices and banks’ financing decisions. This paper was accepted by Gustavo Manso, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2020.03003 .